Prevalence of Pulmonary Tuberculosis among the suspected patients visiting tertiary care hospital in Birgunj, Nepal - Shrestha, S; Shakya, B; Shrestha, P (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Mycobacterial disease continues to cause high morbidity and mortality and is a major public health problem in Nepal. Bacteriological examination of sputum is the cornerstone in the diagnosis of pulmonary tuberculosis in the developing world. This prospective study was carried out with an objective to evaluate the prevalence of pulmonary tuberculosis among the patients visiting National Medical College Teaching Hospital by Ziehl- Neelsen (Zn) staining microscopy. Material and Methods: The study was cross-sectional study. Three consecutive early morning sputum collected from 626 patients were subjected to Zn staining and observed under oil immersion. Results: Among 626 patients, 85 (13.57%) were found to be Acid fast positive by Zn staining microscopy. Of total suspected patients,16.0% of male and 8.7% of female were infected, common among 41-60 years group (17.2%) followed by 21-40 years (12.6%) and multibacillary cases was 71.8%. Conclusion: The prevalence of pulmonary tuberculosis among National medical college teaching hospital was found to be higher than the Nation pulmonary tuberculosis detection rate, most commonly infecting males. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7886 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):48-52